KARAKATAN (ALTERNATIVE MODEL) OF LAND DISPUTE RESOLUTION IN BADAMAI CUSTOMARY IN SOUTH KALIMANTAN - Mohlis, Mohlis; Jalaluddin, Jalaluddin (Proceeding International Seminar of Islamic Studies, 2024)
Land disputes in our lives cannot be avoided, this is due to the shift in the function of land in the economic development development sector, especially with the development of plantations and mining sectors managed by companies which has an impact on the loss of a sense of justice in the people who own the land, leaving disputes/disputes. that land. The karakatan that grows in the Banjar community is a local wisdom that has been embedded for a long time, so that the karakatan can become an alternative model for resolving land disputes in the bamalam custom in South Kalimantan. This research aims to analyze the concept of karakatan as an alternative model in resolving land disputes thoroughly in the bacepat custom in South Kalimantan. The research method used is an empirical legal method with a case study approach in describing it qualitatively. The results of the research found that Karakatan is an alternative model for resolving land disputes in the Badunia custom in accordance with the spirit of article 21 of the Sultan Adam Law which reads: Every kampoeng, if there is a dispute about the content of the kampoengnja ija itoe tetoeha kampungnja koesoeroeh, will discuss the mupaqat-mupaqat of the opponent who toeha-toeha kampoengnja itoe lamoen cannot also discuss the matter and take it to the judge, so the values of local wisdom are very strong, where every time there is a problem in the midst of life the community can be resolved by the village elders, this means that the ishlah carried out by the village elders is none other than to maintain kinship in their environment, meaning that the character of community life becomes a priority in resolving disputes/problems faced by the community.